The Characterization of Beta Chain Fibrinogen (FGB) Gene From Maleo (Macrocephalon Maleo S. Muller 1846) Tuva Village Gumbasa Sub-District Sigi Regency Central Sulawesi - Syam, Zakiah Zulfitri; Budiarsa, I Made; Astija, Astija (Jurnal Riset Pendidikan MIPA, 2019)
The FGB gene is a gene that plays a role in synthesizing b-fibrinogen proteins and is often used as a molecular marker because it is useful for studying bird phylogenetics. The purpose of this study was to describe the character sequences of the FGB gene in Maleo birds (Macrocephalon maleo S. Muller 1864). This study uses laboratory exploratory methods. Alignment is done using the MEGA6 program (Clustal W). Phylogeny trees are constructed based on the Neighbor-Joining algorithm and the Juke-Cantor evolution model of the MEGA6 program. The sample in this study was 0.3 ml of blood from Maleo birds and members of the Megapodiidae group species used as a comparison. The results of this study indicate the length of the FGB 576 bp sequence and was identified with a base composition of 32.2% A, 30.4% T, 17.0% C and 20.3% G. Nucleotide composition of the sequence of Adenine-rich FGB genes. Analysis of the FGB gene sequence phylogeny tree produced a tree topology that was quite good and had the power to split at the interspecies level and place the maleo bird in its own line compared to other Megapoda genera.